Peran Orang tua Dalam Mengenalkan Pendidikan Seks Pada Anak Usia Dini - Candra Nindiya, Devi; Dessy Farantika; Raras Ayu Prawinda (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Sexual education in early childhood does not mean teaching how to have sexual relations, but rather explaining the human body's organs, their functions, and how to care for and maintain them. The presentation is carried out in stages, starting from introducing body parts and reproductive organs and their functions, understanding gender differences, separating children's beds, to teaching the importance of protecting their private parts and eyes. This research applies a qualitative descriptive method involving five parents as subjects, who have children aged 3–5 years in the Perum Griya Permata Alam Kanigoro environment, Blitar Regency. Data was collected through observation, interviews and documentation. Observations were carried out directly to identify the strategies used by parents in introducing sexual education to their children and the way they communicate with their children. Data analysis was carried out using triangulation techniques, which included data reduction, data presentation, verification and drawing conclusions. The research results show that parents apply various strategies in introducing sexual education to children, including: 1) introducing gender differences, 2) introducing sexual organs, 3) teaching toilet training, and 4) instilling shame.